Paternal Postpartum Depression Scale: a systematic literature review - Rosyidah, Hanifatur; Chayani, Sisca Anggun; Aisyaroh, Noveri (Jurnal Kesehatan Ibu dan Anak, 2023)
Postpartum depression in fathers has an impact on the harmony of household relationships, children's emotional development disorders, children's behavior disorders, even children can also be 2-4 times at risk of depression before adulthood. This study aims to review several instruments used to assess fathers' PPD (Postpartum Depression). The database used in this literature review is PubMed. Based on 10 studied, there are 9 different father PPD instruments, including EPDS (Edinburgh Postnatal Depression Scale), GMDS (Gotland Male Depression Scale), BDI (Beck Depression Inventory), BDI-II, GHQ-12 (General Health Questionnaire- 12), PHQ-9 (Patient Health Questionnaire - Depression Module) CES-D (Center for Epidemiological Studies Depression), Zung SAS (Zung's Self-rated Anxiety Scale), and HAD-A (Hospital Anxiety and Depression Scale. EPDS is an instrument most frequently used in detecting paternal PPD, appeared in 10 out of 10 studies. This study concludes that there are 9 different instruments for detecting PPD in the father, and the EPDS is the most frequently used instrument in detecting PPD in the father, which consists of 10 questions with a score limit of 10/11.